2022
DOI: 10.5797/jnet.oa.2021-0090
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Protection against Radiation Dose to Eyes of Operators Performing Neuroendovascular Procedures: A Nationwide Study in Japan

Abstract: Objective: To meet the new standard of the annual dose limit for the eye lens recommended by the International Commission on Radiation Protection, radiation doses of neuroendovascular procedures in Japanese institutions were investigated.Methods: Radiation doses to operators involved in 304 neuroendovascular procedures at 30 Japanese institutions were prospectively surveyed. The institutions recruited at an annual meeting of the Japanese Society for Neuroendovascular Therapy participated voluntarily. A maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The mean operator lens dose per case ranged from 0.019 to 0.800 (median = 0.113) mSv in a literature review of the radiation doses during various procedures, including percutaneous nephrolithotomy, vertebroplasty, orthopedic extremity nailing for the treatment of fractures, biliary tract procedures, transjugular intrahepatic portosystemic shunt creation (TIPS), head/neck endovascular therapeutic procedures, and endoscopic retrograde cholangiopancreatography (ERCP) [9]. A dose survey in Japan for neurovascular interventions revealed that the mean dose of the left eye lens per procedure was 0.088 mGy, or 0.176 mGy if ceiling-mounted shields or lead glasses were not used [10]. In fact, more than 2,000 healthcare workers in Japan, mostly physicians, have had their equivalent dose of the lens exceed 20 mSv per year in 2020 [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The mean operator lens dose per case ranged from 0.019 to 0.800 (median = 0.113) mSv in a literature review of the radiation doses during various procedures, including percutaneous nephrolithotomy, vertebroplasty, orthopedic extremity nailing for the treatment of fractures, biliary tract procedures, transjugular intrahepatic portosystemic shunt creation (TIPS), head/neck endovascular therapeutic procedures, and endoscopic retrograde cholangiopancreatography (ERCP) [9]. A dose survey in Japan for neurovascular interventions revealed that the mean dose of the left eye lens per procedure was 0.088 mGy, or 0.176 mGy if ceiling-mounted shields or lead glasses were not used [10]. In fact, more than 2,000 healthcare workers in Japan, mostly physicians, have had their equivalent dose of the lens exceed 20 mSv per year in 2020 [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is essential to evaluate the lens dose for each patient during INR, as it is one of the most radiosensitive tissues in the human body. [13][14][15][16][17] Direct measurement of the patient's skin dose with thermoluminescent dosimeters or radiophotoluminescent glass dosimeters (RPLDs) was performed during diagnostic angiography and INR. 9,15,[18][19][20][21][22][23] However, these studies did not estimate the peak skin dose (PSD) or the right and left lens doses in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is essential to evaluate the lens dose for each patient during INR, as it is one of the most radiosensitive tissues in the human body. 13 17) …”
Section: Introductionmentioning
confidence: 99%